Definition of Tenuipalpus sensu stricto (Acari, Tenuipalpidae), with redescription of Tenuipalpus caudatus (Dugès) and description of a new species from Costa Rica - Castro, Elizeu B. [UNESP]; Kane, Ethan C.; Feres, Reinaldo J. F. [UNESP]; Ochoa, Ronald; Bauchan, Gary R. (Taylor & Francis, 2016)
The taxonomic history of the genus Tenuipalpus Donnadieu is discussed and Tenuipalpus caudatus (Dugès) (=Tenuipalpus palmatus Donnadieu) is redescribed based on specimens from Portugal intercepted at ports of entry in the United States, and references including photographic records of the neotype of T. caudatus. In addition, a proposed new species, Tenuipalpus erbei sp. nov. is described from Costa Rica. Our results show that T. caudatus, T. erbei sp. nov. and another 36 known species of Tenuipalpus share a pair of lateral body projections associated with setae c3, considered a synapomorphy for the newly defined group, Tenuipalpus sensu stricto. We also show that its members share other character states, although these features are found elsewhere in Tenuipalpus and also in Ultratenuipalpus, indicating their origins are within Tenuipalpus. A list of Tenuipalpus sensu stricto species is presented.
Keywords: body projections; crests; Flat mites; low-temperature scanning electron microscopy; remote-sampling; systematics; taxonomy; Tenuipalpus palmatus Donnadieu